YouTube as an information source of spinal anesthesia, epidural anesthesia and combined spinal and epidural anesthesia - Tulgar,Serkan (2017)
Abstract Introduction Social media as YouTube have become a part of daily life and many studies evaluated health-related YouTube videos. Our aim was to evaluate videos available on YouTube for the conformity to textbook information and their sufficiency as a source for patient information. Material and method A search of the YouTube website was performed using the keywords "spinal anesthesia, epidural anesthesia, combined spinal epidural anesthesia". Firstly, 180 videos were evaluated and the characteristics of the video were noted, and the features of the video too were noted if the video was regarding neuraxial anesthesia. Questionnaire 1 (Q1) evaluating the video quality relating to neuraxial anesthesia was designed using a textbook as reference and questionnaire 2 (Q2) was designed for evaluating patient information. Results After exclusions, 40 videos were included in the study. There was no difference in Q1 or Q2 scores when videos were grouped into 4 quarters according to their appearance order, time since upload or views to length rate (p > 0.05). There was no statistical difference between Q1 or Q2 scores for spinal, epidural or combined videos (p > 0.05). Videos prepared by a healthcare institute have a higher score in both Questionnaires 1 and 2 (10.87 ± 4.28 vs. 5.84 ± 2.90, p = 0.044 and 3.89 ± 5.43 vs. 1.19 ± 3.35, p = 0.01 respectively). Conclusion Videos prepared by institutes, societies, etc. were of higher educational value, but were still very lacking. Videos should be prepared in adherence to available and up-to-date guidelines taking into consideration appropriate step by step explanation of each procedure, patient safety and frequently asked questions.